Analysis Of Carry Fish Supply Chain In Pak Surya Gold Firm Farm, Desa Sampean Kec. Sungai Kanan Kab. Labuhanbatu Selatan - Epa Purnama Sari Harahap; Melati Devyana; Siti Aisyah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this study was to find out how the analysis of the goldfish supply chain at Pak Surya's goldfish farm in Sampean Village, Kec. Right River District. South Labuhanbatu. This study uses a qualitative method in the form of interviews and relevant literature sources, where in the interview method the researcher interviewed resource persons, namely carp livestock business owners. Based on the research that the author conducted, the supply chain process that occurs in the goldfish livestock business at Pak Surya Goldfish Farm, Sampean Village, Kec. Right River District. South Labuhanbatu includes several parties, namely fish seed suppliers - fish farms - markets - local traders - consumers. The farm can also cut the supply chain by directly selling the products of carp livestock to local traders in the vicinity of your village.